IMPACT OF GESTATIONAL DIABETES MELLITUS ON HEMATOLOGICAL PARAMETERS, LIVER FUNCTION, RENAL FUNCTION, AND LIPID PROFILE IN ANTENATAL WOMEN AT A TERTIARY CARE HOSPITAL - Shanmugam, Vijaya Devi; MURUGESAN, Danasegaran; SHRUTHII NANJUNDAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Gestational diabetes mellitus (GDM) is a condition in which glucose intolerance is first recognized during pregnancy. It affects a substantial percentage of pregnancies globally, with a significant prevalence in India. Iron supplementation is often recommended to prevent anemia, but caution is advised in GDM due to the potential inflammatory effects. Elevated hemoglobin (Hb) levels, associated with excess iron, may increase the risk of GDM. This study aims to investigate the differences in Hb and various other blood parameters between controlled and uncontrolled GDM mothers attending antenatal OPD for a regular check-up. Methods: This cross-sectional study was conducted among 100 women diagnosed with GDM at a tertiary care hospital in Western Tamil Nadu after obtaining ethical clearance and informed consent from the participants. Routine blood investigations, like a complete hemogram, HbA1C, renal and liver function tests, and lipid profiles, were recorded. Participants were categorized based on HbA1C values (<6.5 as normal, >6.5 as abnormal). Differences in blood parameters between the two groups were statistically analyzed. Results: The study found no significant differences in age, weight, height, or BMI between the controlled and uncontrolled GDM groups. Mean HbA1c levels were 5.58±0.41 and 6.98±1.23 in controlled and uncontrolled GDM groups, respectively. Comparing hematological parameters, the controlled GDM group exhibited higher mean red blood cell (RBC) levels (4.6±0.69 vs. 4.12±0.92) but lower Hb levels (12.25±2.26 vs. 11.01±3.59) than the uncontrolled GDM group. There were no significant differences in platelet, lymphocyte, and MCH levels. Urea, triglycerides, and globulin levels were higher in the uncontrolled GDM group, but all values remained within normal limits. Conclusion: Elevated Hb levels were associated with uncontrolled GDM, indicating a potential risk factor. The study underscores the importance of monitoring iron levels in GDM patients. In addition, heightened white blood cell counts and altered hematological parameters suggest an inflammatory component in uncontrolled GDM. Further research is warranted to explore these associations and their clinical implications for managing GDM effectively.